Analisis Efisiensi dan Pendapatan Usahatani Kedelai di Kabupaten Garut Provinsi Jawa Barat - Mahabirama, Aditya Kusuma; Kuswanti, Heny; Daryanto, Suwarsinah; Winandi, Ratna (Universitas Brawijaya, Indonesia, 2013)
This study aims to analyze efficiency and revenue in soybean farming. In order to attain the objective, this study uses primary data that are collected from 72 soybean farmers taken purposively. Production factor analysis using Cobb Douglas production function to analyze factors that fect soybean production showed that Male Labor, Seeds and Land Area variables had positive effect; meanwhile, Women Labor had negative effect on soybean farming. Based on the analysis of soybean farming revenue in Garut district, farmers can still earn the cash revenue compared to the cash cost as much as Rp 2,027,455.92 and earn revenue from the total cost of Rp 968,474.41, with R/C ratio of 1:35 and 1:14. R/C ratio value indicates that soybean farming in Garut is still feasible and profitable when cultivated. Efficiency is obtained from a comparison between the Value of Marginal Product and Marginal Cost. The results showed that the production inputs in soybean farming are not yet efficient. MaleLabor and Manure should be reduced from 89.76 HOK; 591.04 Kg to 80.67 HOK; 115.52 Kg. In addition, Female Labor and Chemical Fertilizer should not be used since it causes more losses due to using these inputs. Pesticides, Seeds and Land Area inputs shall be increased from 709.70 ml; 77.27 Kg; 0.35 to 241.98 ml; 297.43 Kg; 9.77 Ha.